A framework for user-generated geographic content acquisition in an age of crowdsourcing. Issue 2 (4th March 2017) - Xu, Jinghai; Nyerges, Timothy L.
ABSTRACT: Obtaining useful geographic information from the flood of user-generated geographic content (UGGC) data is of significant interest, but comes with challenges in an age of crowdsourcing. To address this issue, we adopt Maslow's model of human needs to frame UGGC. Synthesizing across literature about volunteered geographic information and participatory GIS, we present a conceptual framework for characterizing collection of UGGC. The framework is composed of multiple dimensions and levels that include perspectives about motivations, participatory methods, and participants. We also articulate four levels of participants (stakeholders, core-engaged participants, semi-core-engaged participants, and engaged citizens) together with four work principles (communication, cooperation, coordination, and collaboration). Finally, a case study describes an example we use to evaluate the conceptual framework for its suitability in design of a UGGC system. We conclude by reflecting on how and why this framework offers a valuable perspective for deriving useful geographic information and offer future research directions.